2017
DOI: 10.1016/j.pmn.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Pain in Patients Diagnosed with Depression and Heart Failure

Abstract: Background Heart failure (HF) is a costly and growing health problem that is routinely complicated by chronic pain and depression. The purpose of this paper is to describe the characteristics of pain and pain management in depressed HF patients. Design/Participants In this descriptive cross-sectional study, we analyzed data from 62 participants with depression and Class II–IV HF. Study variables of interest were collected from the Brief Pain Inventory, Beck Depression Inventory, and Rand-36. Results Almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…The number of primary complaints of chest pain and other locations of pain was examined. In previous research, chest pain accounted for 13% to 42% of pain symptoms experienced by outpatients with HF 10,17,22 . In the parent study, 65% of patients reported chest pain on index transport, independent of having a primary complaint of pain (22.2%) 28 .…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The number of primary complaints of chest pain and other locations of pain was examined. In previous research, chest pain accounted for 13% to 42% of pain symptoms experienced by outpatients with HF 10,17,22 . In the parent study, 65% of patients reported chest pain on index transport, independent of having a primary complaint of pain (22.2%) 28 .…”
Section: Discussionmentioning
confidence: 80%
“…Binomial logistic regression was used to evaluate variables associated with presenting with a primary complaint of pain. Variables included in the logistic regression analyses were age, self-reported gender (woman, man); self-reported race (White, Black, Other); shortness of breath; number of comorbid conditions; number of medications; history of coronary artery disease, atrial fibrillation, coronary artery bypass graft, or myocardial infarction; and presence of a pacemaker or implantable cardioverter-defibrillator 7,11,13,20,22–28,33–35 . Ethnicity and history of sudden cardiac arrest were excluded from the regression analysis because of small sample sizes (n < 50 per group).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a descriptive cross‐sectional study with 62 CHF patients with NYHA class II‐IV, pain was frequently observed. 50 Ninety‐eight per cent of the patients described unspecified pain in the past month, and 66% had pain in the last 24 h. The character of pain in 1886 CHF patients was assessed in another interventional study. Eighty per cent of patients reported at least some chest pain, and the authors concluded that it was unlikely only due to angina pectoris 51 .…”
Section: Painmentioning
confidence: 99%